BUDAYA JAWA DALAM DIASPORA: TINJAUAN PADA MASYARAKAT JAWA DI SURINAME - - Darmoko (JURNAL IKADBUDI, 2016)
Javanese society and culture has been forged by the situation and condition of the times centuries. Cultural influences from outside, such as the Hindu - Buddhist, Islamic, Chinese, and European, indigenous cultures should lead to "adapt", the acculturation strategy. Local genius to filter incoming external cultural influence of local culture. Javanese culture and society continues to change, whether caused by external and internal factors.Policy and socio-economic problems caused the population of a particular region should move. Dutch colonial period to independence there has been a migration of people from rural to urban areas of Java, from a rural island to another, and from a village in Indonesia to foreign countries. In new areas of the Javanese form a new community as the Javanese developed overseas and that's where Javanese culture that was once their preserve, coached, and developed, such as the Java community in Jakarta, Deli Serdang - North Sumatra, Sitiyung - west Sumatra, Lampung, and Suriname. Java community in this new place coexist and mingle with other tribes and not seldom of those who later married and have children and grandchildren .In the early days of the country Suriname frequent conflicts between tribes that are in there. Suriname Javanese people often act as peacemaker for the tribes opposing it. Javanese cultural values operate to defuse a tense situation and soften the situation and condition of the nuances of violence. The value of local knowledge of Java can be used as an "heirloom" wherever people are and in what circumstances they experience. The value of local knowledge of Java prioritize a sense of leadership and uphold the principles of equality and harmony and respect. This paper aims to explore the value of indigenous leadership that operates on Java Javanese in Suriname. Results will be achieved this paper determined the value of local knowledge is Java - oriented leadership as a solution for the value of a conflicts in society.Keywords : Java, culture, values, diaspora, Suriname